QT/QTc study conducted in Japanese adult healthy subjects: A novel xanthine oxidase inhibitor topiroxostat was not associated with QT prolongation. (22nd November 2013) - Sugiyama, Atsushi; Hashimoto, Hiroya; Nakamura, Yuji; Fujita, Tomoe; Kumagai, Yuji
Abstract A QT/QTc study was conducted in compliance with ICH E14 guideline to evaluate the effects of a new xanthine oxidase inhibitor topiroxostat in Japanese healthy subjects. Forty‐eight Japanese healthy subjects (males 24; females 24) received a single oral dose of topiroxostat (60 or 180 mg), moxifloxacin (400 mg) or placebo in a single‐center, double‐blind, four‐period crossover design. Fridericia's formula (QTcF = QT/RR0.33) was used as a primary method for QT‐interval correction. The mean QTcF was prolonged by moxifloxacin, of which largest time‐matched difference from placebo administration was 13.6 milliseconds with 90% confidence interval (CI) of 11.2 and 15.9 milliseconds at 4 hours post‐dose. The mean QTcF was hardly affected by either dose of topiroxostat, of which largest time‐matched difference from placebo administration was 2.9 milliseconds with 90% CI of 0.6 and 5.3 milliseconds at 4 hours post‐dose for 60 mg, and 2.3 milliseconds with 90% CI of 0 and 4.7 milliseconds at 1 hour post‐dose for 180 mg. The results were essentially the same in the sex subgroup analysis. Moxifloxacin can be used as a positive control for QT/QTc studies in Japanese subjects; and topiroxostat may not cause QT‐interval prolongation in males as well as females.